2019
DOI: 10.1136/bmjopen-2019-033905
|View full text |Cite
|
Sign up to set email alerts
|

Palliative and end of life care in prisons: a mixed-methods rapid review of the literature from 2014–2018

Abstract: ObjectivesTo explore current practice in relation to palliative and end of life care in prisons, and to make recommendations for its future provision.DesignA rapid literature review of studies using qualitative, quantitative and mixed-methods, with a narrative synthesis of results.Data sourcesSix databases searched between January 2014 to December 2018: ASSIA, CINAHL, Embase, MEDLINE, National Criminal Justice Reference Service Abstracts and Scopus.Eligibility criteriaPrimary research articles reporting qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 38 publications
0
31
0
1
Order By: Relevance
“…It is not possible to conclude from this study whether the support provided by hospices is adequate to meet the needs of those who may die in Scotland’s prisons; further research will be required to evaluate this. However, hospice support for prisons in Scotland is at an early stage in its development, and ageing and dying while incarcerated is still a common fear for many people in prison, 11 partly due to worries about the perceived inadequacy of palliative care provision. 34 Unmet healthcare needs are a common feature for those who are in prison, both during and at the end of life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is not possible to conclude from this study whether the support provided by hospices is adequate to meet the needs of those who may die in Scotland’s prisons; further research will be required to evaluate this. However, hospice support for prisons in Scotland is at an early stage in its development, and ageing and dying while incarcerated is still a common fear for many people in prison, 11 partly due to worries about the perceived inadequacy of palliative care provision. 34 Unmet healthcare needs are a common feature for those who are in prison, both during and at the end of life.…”
Section: Discussionmentioning
confidence: 99%
“…Approaches to delivering palliative care in prisons vary between countries, and include (but are not limited to) dedicated hospices within the prison walls, and support from specialist palliative care providers outside the prison. Much of the literature on palliative care in prisons comes from the USA, 1 , 11 where prison-based hospices are comparatively common. 10 In contrast, a recent international mapping exercise by the European Association of Palliative Care (EAPC) indicated that there were no prison hospices in Australia, Belgium, Czech Republic, France, Portugal or Slovakia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A qualitative methodology is used in this study, comprising a short literature review building upon the existing literature described in McParland and Johnston (2019) and through analysis of PPO reports. The data collection and analysis is comprised of five stages: -…”
Section: Methodsmentioning
confidence: 99%
“…In their mixed-methods, rapid review of the literature, McParland and Johnston (2019) seek to explore the current practices of palliative and end of life care in prisons and make recommendations for improvement in prisoner care. The review engages with the prisoner voice, their families, prison officers and prison healthcare staff as the basis for generating insights into;…”
Section: Mcparland and Johnston (2019)mentioning
confidence: 99%